2021
DOI: 10.3390/antibiotics10091107
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Literacy, Knowledge, and Awareness Regarding Antibiotic Use and Antimicrobial Resistance during the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Multi-drug-resistant (MDR) organisms pose a global threat to modern medicine, which has grown as a result of irrational antibiotic use and misuse. This study aimed to assess general public knowledge in Jordan and awareness of antibiotics and antibiotic resistance during the COVID-19 pandemic. A cross-sectional study was carried out utilizing the WHO multicountry public awareness survey. The study population was composed mainly of social media users, and a total of 1213 participants completed the online survey.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 54 publications
(88 reference statements)
0
9
0
Order By: Relevance
“…Most of the respondents (72%) correctly believed that this was a false statement (i.e., they believed Abs resistance was a problem in Saudi Arabia). In contrast, in the Jordanian study where participants had either heard or not heard about Abs resistance, 53% believed that Abs resistance was a problem in other countries but not in Jordan [4]. Similarly, in Kuwait, nearly more than half of the participants disagreed that Abs resistance was a worldwide issue [18].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Most of the respondents (72%) correctly believed that this was a false statement (i.e., they believed Abs resistance was a problem in Saudi Arabia). In contrast, in the Jordanian study where participants had either heard or not heard about Abs resistance, 53% believed that Abs resistance was a problem in other countries but not in Jordan [4]. Similarly, in Kuwait, nearly more than half of the participants disagreed that Abs resistance was a worldwide issue [18].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, the main source for Abs in our study was a pharmacy (82%), and only a few of the participants (8%) obtained Abs from family or friends. In Jordan, a country that has no such obligations regarding Abs use, a study that was recently conducted in 2021 found that although pharmacies represented the source of Abs for approximately half of the participants, approximately 24% obtained Abs from a family member or a friend [4]. Thus, national regulations regarding Abs use must be continued and effectively monitored in Saudi Arabia, a country that has religious seasons and great challenges of welcoming millions of people periodically [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of such geographical location specific data retrieved from web searches helps the health authorities implement appropriate and timely actions. Via social media networking, public health researchers or clinicians have access to a wide/global audience (Figure 1) [38,39]. This allows the rapid communication of health-related information and might contribute to the improvement of the society's health status.…”
Section: Social Media's Impact On Health Care Systemmentioning
confidence: 99%
“…Several strategies, such as different assessments or educational programs, have been implemented to increase knowledge concerning antibiotic use and infectious diseases [47]. Among a variety of tools, social networking platforms such as Facebook pages, Twitter and YouTube have been efficiently used change public perception (Figure 1) [39,50,51]. The dissemination of an educational program called "antimicrobial stewardship" (ASP) on Facebook and Twitter for students of medicine is a worthy example of the application of social media technologies [50,52].…”
Section: Social Media's Impact On Health Care Systemmentioning
confidence: 99%